Free-standing dual-network red phosphorus@porous multichannel carbon nanofibers/carbon nanotubes as a stable anode for lithium-ion batteries. (1st November 2019) - Liang, Shuaitong; Pei, Xiaoyuan; Jiang, Wanwei; Xu, Zhiwei; Wang, Wei; Teng, Kunyue; Wang, Chunhong; Fu, Hongjun; Zhang, Xingxiang
Abstract: Red phosphorus (P) suffers from dramatic capacity decay and poor conductivity as anodes for lithium-ion batteries (LIBs). Recently, the composite material made of red phosphorus and carbon matrix has become the mainstream route to solve these problems. In this work, we prepared a free-standing flexible P/C electrode by encapsulating phosphorus in a dual-conducting network of porous multichannel carbon nanofibers and in-situ carbon nanotubes (denoted as P@PMCNFs/CNTs) to achieve electrode conductivity and cycle stability. The nano-sized red P is adsorbed in three-dimensional carbon network and channel according to strong P–C chemical bond adsorption energy. Furthermore, the free-standing electrode can make full use of the overall capacity of the material and avoid inactive additives, which improving the overall volume functional density. When used as anodes for LIBs, the prepared free-standing P@PMCNFs/CNTs electrode shows excellent rate capability (601 mA h g −1  at 3 A g −1 ), cycle stability (802.3 mA h g −1  at 1 A g −1 after 500 cycle), and a surface-dominated contribution (70.2%). Graphical abstract: Image 1 Highlights: Red phosphorus@porous multichannel carbon nanofibers/carbon nanotubes was prepared. The dual-network composite provides more channels that facilitate charge transport. Dual-network increases the contact between electrolyte and carbon-based active sites. The cyclic stability of phosphorus/carbon composite has been significantly improved.